DENTITION CHANGES IN GENETIC DISEASES - Carmen Galea; Dorin Ioan Cocoș; Eniko Gabriela Papp; Radu Mircea Sireteanu Cucui; Sorana Maria Bucur (Romanian Society of Oral Rehabilitation, 2024)
This paperwork aims to identify the dentition's changes in genetic diseases and to find solutions to solve them. Method: We studied 31 patients with different genetic diseases (Down syndrome, Turner syndrome, Prader-Willy syndrome, Bardet-Biel syndrome, Tourette syndrome , Pfeiffer syndrome,and schizophrenia ). The patients were of school age (7-14 years old) and followed socialization programs within a foundation, the study taking place over 1 year). Conclusion: the most frequent cases were represented by dental malocclusion (98,16%), correlated with mental retardation and facial dysmorphism (74,2%), shape and structure anomalies (76,11%), mandibular hypoplasia (33,3%) and 6% pigmentation on the mucous membranes. Conclusions: We believe that the health education of parents with rare genetic diseases that affect skeletal development should be emphasized in order to ensure better oral health in this group. The health system should develop screening strategies and education and support services. Also, access to dental treatments for patients with rare genetic diseases should be supported through various programs.